Anna Negri, una regista in cerca d’identità - Jacoponi, Tiziana (Incontri. Rivista europea di studi italiani, 2012)
Anna Negri, a Director in Search of an Identity   The transition to an autobiographical novel format in 2009 is the illustration, on paper, of a personal and intimate narrative that offers the reader a definition of cinescrittura (cinematic writing). Moreover, this evolution illustrates how the language of television and film has influenced Anna Negri’s narrative and stylistic choices in prose. The reading of the filmic image demands, as in the reading of a textual passage, a fundamental decoding of linguistic, ethical, aesthetic, and narrative processes Additionally and above all, one must also analyse the emotional system at work in the narrative, as it is the emotional area that is most stressed when both watching a film, and when reading a book (for instance when reading a book so compelling that one cannot put it aside until done). That is to say, the narrative’s emotional system emotionally involves the reader or viewer, causing him or her to interact with images and stories. Negri’s literary-cinematic production favors an abundance of dialogue, fast beats, contamination between different genres such as autobiography and mockmumentary, the use of musical and film vocabulary, intermixed with dialect. When directly confronted with this array of aspects, the viewer-reader’s task is to decode and interpret. In Con un piede impigliato nella storia Anna Negri succeeds in condensing the wish to offer a space to dream, by using cinematic writing as a means of making concrete references, in private or collective memory, to the personal and social history of her country. The stylistic choice of dialect, or of a ‘foreign’ cadence, serves to render the text/film more accessible. The viewer/reader both imagines the film when reading the book, and reads textually while watching the film.